2020
DOI: 10.51135/agh.v11i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Sifat Fisis Kayu Bintangur (Calophyllum Soulattri Brum.f.) Asal Makbon Kota Sorong

Abstract: Penelitian ini bertujuan untuk mengetahui variasi kerapatan dan kadar air basah berdasarkan posisi vertikal dan horisontal. Kayu bintangur dipilih dari tegakan yang baik dan tanpa cacat dan ditebang sebanyak 2 pohon. Setelah ditebang, kemudian dibuat contoh uji dari bagian bawah, tengah dan ujung batang. Bagian bawah berjarak 50 cm dari tanah, sedangkan jarak dari bagian bawah ke bagian tengah dan bagian tengah ke bagian ujung masing-masing adalah 4 meter. Contoh uji dipotong berbentuk disk dengan tebal 15 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It can be concluded that trees store more biomass content than oil palm because the forest area itself has a larger height and diameter than oil palm plants. According to [12], states that the biomass owned by the trunk is quite large compared to other parts because the woody part and the place to store food reserves from photosynthesis are used to grow both vertically (high) and horizontally (diameter).…”
Section: Aboveground Biomass Estimationmentioning
confidence: 99%
“…It can be concluded that trees store more biomass content than oil palm because the forest area itself has a larger height and diameter than oil palm plants. According to [12], states that the biomass owned by the trunk is quite large compared to other parts because the woody part and the place to store food reserves from photosynthesis are used to grow both vertically (high) and horizontally (diameter).…”
Section: Aboveground Biomass Estimationmentioning
confidence: 99%